برنامج إرشادي قائم على الإرشاد العقلاني الانفعالي السلوكي لرفع مستوى تقدير الذات وتحسين مستوى التحصيل الدراسي لدى التلاميذ المعيدين (مجلة الواحات للبحوث والدراسات, 2021)
The Current Research Aims At Building A Mentoring Program Based On Emotional And Behavioral Guidance To Raise The Level Of Self-Esteem And Improve The Pedagogical Achievement Of The Students Of Fourth Year In Middle Schools. The Researcher Built The Program According To The Theory Of Albert Ellis, As Well As A Sample Of Previous Studies Related To The Subject.The Program Was Presented To A Number Of Teachers And Specialists In The Field Of Guidance And Their Views Have Been Taken Into Consideration, And Then The Final Version Of The Program Was Approved In Accordance With The Sample That Was Built On Them. key words-Counseling, rational counseling, emotional behavior, academic achievement